Kritik Terhadap Epistemologi Fikih Murtad. - Sofyan A.P Kau; Zulkarnain Sulaeman (AHKAM : Jurnal Ilmu Syariah, 2016)
This paper contains a critique to fiqh of apostasy which considers the action as a criminal offense to be sentenced to death. Reviewing the legal sources of fiqh using allegorical approach and historical evidence indicates that the action is a violation of the theological apostasy against God, and therefore only God who has a right to punish. In al-Qur’an, the type of punishment is non-physical punishment and will be executed in hereafter. The act of apostasy will be punishable by death if apostasy is in political arena and civil matter, which is followed by resistance and rebellion against legitimate political authority that interfere with public safety and official authority. Therefore, the provision of the punishment is handed over to the legitimate political institutions (ta’zir) to determine the appropriate punishment.DOI: 10.15408/ajis.v16i1.2895